Hxt-Carrier-Mediated Glucose Efflux upon Exposure of Saccharomyces cerevisiae to Excess Maltose - Jansen, Mickel L. A. (American Society for Microbiology, 2002)
When wild-type Saccharomyces cerevisiae strains pregrown in maltose-limited chemostat cultures were exposed to excess maltose, release of glucose into the external medium was observed. Control experiments confirmed that glucose release was not caused by cell lysis or extracellular maltose hydrolysis. To test the hypothesis that glucose efflux involved plasma membrane glucose transporters, experiments were performed with an S. cerevisiae strain in which all members of the hexose transporter (HXT) gene family had been eliminated and with an isogenic reference strain. Glucose efflux was virtually eliminated in the hexose-transport-deficient strain. This constitutes experimental proof that Hxt transporters facilitate export of glucose from S. cerevisiae cells. After exposure of the hexose-transport-deficient strain to excess maltose, an increase in the intracellular glucose level was observed, while the concentrations of glucose 6-phosphate and ATP remained relatively low. These results demonstrate that glucose efflux can occur as a result of uncoordinated expression of the initial steps of maltose metabolism and the subsequent reactions in glucose dissimilation. This is a relevant phenomenon for selection of maltose-constitutive strains for baking and brewing.